Biomarkers of Tuberculous Meningitis and Pediatric Human Immunodeficiency Virus on the African Continent - Teunissen, Charlotte Elisabeth; Rohlwink, Ursula; Pajkrt, Dasja; Naudé, Petrus J. W. (Frontiers in Neurology, 2022)
Biomarkers in body fluids are helpful objective tools in diagnosis, prognosis and monitoring of (therapeutic) responses of many neurological diseases. Cerebrospinal fluid (CSF) biomarkers are part of the diagnostic toolbox for infectious neurological diseases. Tuberculous meningitis (TBM) and Human immunodeficiency virus (HIV), are important burdens of disease in Africa and can negatively affect brain health. Two thirds of the world's population of people living with HIV reside in sub-Saharan Africa and 25% of the global burden of tuberculosis (TB) is carried by the African continent. Neuroinflammation and damage of specific neuronal cell types are key constituents in the pathophysiology of these central nervous system (CNS) diseases, and important potential sources of circulating biomarkers. In this review, we summarize current research in the use of biomarkers in TBM and pediatric HIV as case demonstrations for high prevalence neurological diseases in Africa. Inflammatory molecules, primarily when detected in CSF, appear to have diagnostic value in these diseases, especially when measured as profiles. Brain injury molecules, such as S100, Neuron specific enolase and glial fibrillary acidic protein may have prognostic value in TBM, but more studies are needed. There is a need for more cost-economic and high sensitivity technologies to drive further biomarker discoveries and translate into healthcare improvements for these important healthcare problems in a globally fair way.